Naẓariyyah al-Ma'rifah fī at-Tafsīr al-'Ilmi li al-Qurān al-Karīm: نظرية المعرفة في التفسير العلمي للقرآن الكريم - Maulana, Achmad Ilham; Arifinsyah, Arifinsyah; Husein, Muhammad (ZAD Al-Mufassirin, 2023)
Exegesis of Scientific nowadays has become a lot of discussion, including about the pros and cons around the methodology of interpreting science, the second is about the dichotomic phenomenon between scientific truth and the truth of the Qur'an or secularization in understanding the Qur'an, the above problems can be classified into two part, the first is an internal problem, the second is an external problem. This research is a literature study, a qualitative model with critical-reflective analysis. The results of this study are that the interpretation of science is not the interpretation that negates the interpretation of the previous scholars and changes it to a new one, nor does it desacralize the verses of the Qur'an, but its position is as an addition and expansion of the classical interpretation, with some terms and conditions as commentators with a style science.